Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1073/pnas.1003478107
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for SH3 domain regulation of F-BAR–mediated membrane deformation

Abstract: Members of the Bin/amphiphysin/Rvs (BAR) domain protein superfamily are involved in membrane remodeling in various cellular pathways ranging from endocytic vesicle and T-tubule formation to cell migration and neuromorphogenesis. Membrane curvature induction and stabilization are encoded within the BAR or Fer-CIP4 homology-BAR (F-BAR) domains, α-helical coiled coils that dimerize into membrane-binding modules. BAR/F-BAR domain proteins often contain an SH3 domain, which recruits binding partners such as the oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
183
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(203 citation statements)
references
References 36 publications
(62 reference statements)
19
183
0
Order By: Relevance
“…The interaction between PACSIN1 and PICK1 was enhanced by the SH3-domain deletion (Fig. 4B, lane 4), consistent with two earlier studies describing an intramolecular interaction between the F-BAR and the SH3 domains that inhibits PACSIN1 function (18,28). Surprisingly, we also found that the GFP-PACSIN1-ΔF-BAR domain [variable region (VAR) + SH3] was able to bind myc-PICK1 robustly (Fig.…”
Section: Pacsin Interacts With Pick1supporting
confidence: 81%
See 1 more Smart Citation
“…The interaction between PACSIN1 and PICK1 was enhanced by the SH3-domain deletion (Fig. 4B, lane 4), consistent with two earlier studies describing an intramolecular interaction between the F-BAR and the SH3 domains that inhibits PACSIN1 function (18,28). Surprisingly, we also found that the GFP-PACSIN1-ΔF-BAR domain [variable region (VAR) + SH3] was able to bind myc-PICK1 robustly (Fig.…”
Section: Pacsin Interacts With Pick1supporting
confidence: 81%
“…Both PICK1 and PACSIN1 share some structural features in that they are subjected to intramolecular interactions, which allow them to exist in "open" or "closed" conformations, and they can interact with actin cytoskeleton regulators, the Arp2/3 complex, and N-WASP, respectively (18,28,41,42). Our domain-mapping analysis showed that the binding to PICK1 is mediated by the variable region in PACSIN1, leaving the SH3 domain available to bind to endocytic proteins and actin-reorganizing molecules.…”
Section: Discussionmentioning
confidence: 99%
“…2), a mechanochemical enzyme recruited to endocytic sites by interaction with SH3 domain proteins 58,59 , including intersectin [60][61][62] , amphiphysin 63 , endophilin 64,65 and syndapin 66 , suggesting a tight interplay between BAR-SH3 protein-mediated membrane deformation (FIG. 2) and dynamin-catalyzed fission 58,67 . In agreement with this, dynamin 1 knockout mice exhibit a striking, activity-dependent accumulation of tubular coated endocytic intermediates 48 .…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
“…WASp itself is autoregulated by inhibitory interactions between its N terminus and its C-terminal Arp2/3-activating verprolin-central-acidic (VCA) domain, and can be activated by the combined effects of SH3 domain-containing binding partners, charged phospholipids, Rho family GTPases, and induced multimerization (6). For several BAR family members, including Syndapin, Amphiphysin, and Nervous Wreck (Nwk), C-terminal SH3 domains also bind directly to the BAR domain, inhibiting membrane association (7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%